PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 3 PADANG - Safany, Putri Wulan; Tasman, Fridgo (Jurnal Edukasi dan Penelitian Matematika, 2024)
The preliminary exam results indicated that the 11th grade students at SMAN 3 Padang exhibited a comparatively low level of proficiency in mathematical problem-solving skills across all indicators. This is a result of insufficient engagement in the learning process. Consequently, an investigation was carried out utilising the Discovery Learning (DL) approach to enhance this capability. The methodology employed was a Quasi Experiment with an appropriate study design. Design utilising a posttest only control group that is not equal. Upon doing a t-test on the data from the sample class, with a significance threshold of α = 0.05, a P-value of 0.001 was achieved. This outcome signifies the dismissal of the null hypothesis (H0). These findings suggest that students using the DL model exhibit superior aptitude compared to those using the direct learning model in class XI at SMAN 3 Padang.Keywords– Mathematical problem solving abilities, Discovery Learning